ChlamBase: a curated model organism database for the Chlamydia research community. (15th April 2019) - Putman, Tim; Hybiske, Kevin; Jow, Derek; Afrasiabi, Cyrus; Lelong, Sebastien; Cano, Marco Alvarado; Stupp, Gregory S; Waagmeester, Andra; Good, Benjamin M; Wu, Chunlei; Su, Andrew I
Abstract: The accelerating growth of genomic and proteomic information for Chlamydia species, coupled with unique biological aspects of these pathogens, necessitates bioinformatic tools and features that are not provided by major public databases. To meet these growing needs, we developed ChlamBase, a model organism database for Chlamydia that is built upon the WikiGenomes application framework, and Wikidata, a community-curated database. ChlamBase was designed to serve as a central access point for genomic and proteomic information for the Chlamydia research community. ChlamBase integrates information from numerous external databases, as well as important data extracted from the literature that are otherwise not available in structured formats that are easy to use. In addition, a key feature of ChlamBase is that it empowers users in the field to contribute new annotations and data as the field advances with continued discoveries. ChlamBase is freely and publicly available at chlambase.org .